Análisis comparativo de softwares open source basados en la gestión de ventas a clientes y control de proveedores en la Distribuidora Álvarez en la ciudad de Babahoyo. - Duche Peñafiel, Vicente Emanuel (2022)
In the present study, the improvement of two important processes for the value chain of the Álvarez distributor has been developed. The processes that have been analyzed are: the customer service management process and the supplier management management process. Currently the organization does not have formally defined processes, owners and controls for each one, the same ones that are described in the process improvement proposal. Another important factor is the study or comparative analysis of free software tools for the automation of the aforementioned processes, which allows control and thus contributes to their improvement. An analysis of the current process handled by the Álvarez distributor in the management of customer service, sales and control of suppliers within the company has been carried out. An analysis of the free software tools or existing in the market that will allow to automate the processes is carried out; according to the functional technological requirements raised, for the incorporation of certain tools in the company in order to obtain an accurate conclusion about the perceived performance of the software, so that in this way, the administrator is better able to contribute actively with all the tasks that aim to achieve the long-awaited customer satisfaction.